(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The year 1258 represents a decisive junction in the history of Bologna: the city was a true regional power, which was preparing to achieve full control over Romagna. The waves of bad weather caused by the eruption of the Samalas volcano, however, caused an important famine that was aggravated by the commercial blockade imposed by Venice, interested in ousting its rivals from the region and acquiring full hegemony in Romagna. Within the city of Bologna, the emergency had many political repercussions: it was especially ridden by the people, who exploited it to gain more power within the political space and to accredit in the eyes of citizenship as the only subject able to pursue the public good. From this conflict were born the Ordinamenta bladi, that is the first systematic legislation on the subject of food that was issued in 1259, whose analysis allows to understand within what limits and with what measures the famine was addressed.